SISTEM TRANSAKSI E-COMMERCE DALAM PERSPEKTIF KUH PERDATA DAN HUKUM ISLAM - Santoso, Sugeng (Ahkam: Jurnal Hukum Islam, 2016)
Trading transactions are not only done conventionally, where buyers and sellers meet face to face. Now the transaction has been switched into cyber-spaced transaction, where the trading transactions are conducted through social networking, computers, mobile phones, etc. Such Transactions are called online trading transactions (e-commerce). According to Islamic law e – commerce transaction should also meet some required conditions such as employers in online commerce (e-commerce) are qualified to be taxable income. But if the income tax law that is used in the taxation for online commerce transactions (e-commerce) is employed, the tax will not be able to be maximized because basically e-commerce transactions are very different from conventional trading transactions. So the need for new rules to serve as a legal basis of the taxation of income in e-commerce transactions is emerging. Kata kunci: Sistem Transaksi, E-Commerce, KUH Perdata, Hukum Islam